(untitled) (ENTHYMEMA, 2023)
The humanist and Dominican nun Juliana Morell (1594-1653) played a particular role as a teacher, writer and translator in the French Counter-Reformation. A polyglot who had studied philosophy, theology and jurisprudence, she composed spiritual works and made two Latin-to-French translations with commentaries: Vincent Ferrer’s Treatise on the Spiritual Life (1350-1419), which had two editions (1617 and 1619), and Augustine’s Rule, published posthumously in 1680. In addition, her Exercices spirituels sur l’éternité (1637) includes translations and exegesis of biblical passages. Reading, and especially translation, understood as spiritual dialogue leading to prayer, were part of her work as a teacher of novice nuns, and she published her writings, complying with the obligation of obedience, so that readers could converse with and spend time in the company of the souls whose words were read and translated.